2011
DOI: 10.1210/en.2010-0858
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin-Stimulated Glucose Uptake in Rat White Adipose Tissue upon Chronic Central Leptin Infusion: Effects on Adiposity

Abstract: Leptin enhances the glucose utilization in most insulin target tissues and paradoxically decreases it in white adipose tissue (WAT), but knowledge of the mechanisms underlying the inhibitory effect of central leptin on the insulin-dependent glucose uptake in WAT is limited. After 7 d intracerebroventricular leptin treatment (0.2 g/d) of rats, the overall insulin sensitivity and the responsiveness of WAT after acute in vivo insulin administration were analyzed. We also performed unilateral WAT denervation to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
(70 reference statements)
4
12
1
Order By: Relevance
“…[ 3 H]-2-deoxyglucose uptake in mouse epididymal adipose tissue was determined immediately after death, as described previously (27,28). Adipose tissue (50 mg) was preincubated for 10 min at 37°C in 1 ml of Krebs-Ringer-HEPES (KRH) buffer (50 mM HEPES, pH 7.4; 137 mM NaCl; 4.8 mM KCl; 1.85 mM CaCl 2 ; and 1.3 mM MgSO 4 ), also used for subsequent incubations.…”
Section: Glucose Uptake In Mouse Wat Explantsmentioning
confidence: 99%
“…[ 3 H]-2-deoxyglucose uptake in mouse epididymal adipose tissue was determined immediately after death, as described previously (27,28). Adipose tissue (50 mg) was preincubated for 10 min at 37°C in 1 ml of Krebs-Ringer-HEPES (KRH) buffer (50 mM HEPES, pH 7.4; 137 mM NaCl; 4.8 mM KCl; 1.85 mM CaCl 2 ; and 1.3 mM MgSO 4 ), also used for subsequent incubations.…”
Section: Glucose Uptake In Mouse Wat Explantsmentioning
confidence: 99%
“…Glucose uptake in WAT explants was evaluated as reported (19). Briefly, fat pad explants (20 mg), after exclusion of visible connective tissue and vessels, were placed in 0.…”
Section: Glucose Uptake In Wat Explantsmentioning
confidence: 99%
“…Furthermore, intracerebroventricular leptin injections in Wistar rats induced SOCS-3 expression and protein levels in adipose tissue, contributing to reduce the insulin response from this tissue [4]. Our results show that the mRNA levels of leptin are significantly increased by s-resistin and especially by the resistin isoform, concomitantly with the increase in SOCS-3 levels, indicating the important role of resistin isoforms in the development of adipocyte leptin resistance.…”
Section: Discussionmentioning
confidence: 57%
“…There are several studies analyzing the effect of insulin on resistin expression in adipose tissue [3,4], in isolated adipocytes and in 3T3-L1 cells [12,17]. Specifically, it has been reported that insulin inhibits resistin expression in 3T3-L1 adipocytes, even at subphysiological concentrations [12].…”
Section: Discussionmentioning
confidence: 99%